Industrial design techniques and materials - Grenier, Jean.; Guidot, Raymond; Salomon, Jean-Jacques.; Toulard, Jean-Baptiste. (: Flammarion, 2006)
This comprehensive work traces the history of design materials, from the origins of mass production during the Industrial Revolution to contemporary use of wood, metals, and synthetics as well as their potential applications for the future. This exhaustive reference covers late nineteenth-century design implications, contemporary design materials and their uses, and design trends$1 (Bfrom the influences of information technology on design conception to ecological design considerations. Raymond Guidot (editor), an eminent design theorist, has organized exhibitions at the Centre Georges Pompidou's Center for Industrial Creation and he has written and contributed to numerous books and exhibition catalogs on design.s
Keywords: Computer-aided design; Design and technology; Industrial design; Materials--Technological innovations